Intensification oof Livestock production by smallholder and landless farmers in India - Das, K S; Singh, A K; Mondal, S K; Rahman, F H; De, H K; Pal, P P; Roy, S K (Indian Farming, 2017)
From the available facts and figures, it is evident that livestock sector is the backbone of Indian agrarian economy which is mainly dependant on small holders and landless farmers. The wide variety of livestock species has the capability to produce at their optimum level if they are managed properly. Therefore, a holistic approach is required at every different levels to meet out the future demand of animals products, to solve the challenges and to safeguard the poor livestock producers.